International comparisons in health economics: Evidence from aging studies - James Banks; James P. Smith (Institute for the Study of Labor (IZA), 2012)
We provide an overview of the growing literature that uses micro-level data from multiple countries to investigate health outcomes, and their link to socioeconomic factors, at older ages. Since the data are at a comparatively young stage, much of the analysis is at an early stage and limited to a handful of countries, with analysis for the US and England being the most common. What is immediately apparent as we get better measures is that health differences between countries amongst those at older ages are real and large. Countries are ranked differently according to whether one considers life-expectancy, prevalence or incidence of one condition or another. And the magnitude of international disparities may vary according to whether measures utilize doctor diagnosed conditions or biomarker-based indicators of disease and poor health. But one key finding emerges - the US ranks poorly on all indicators with the exception of self-reported subjective health status.
urn:nbn:de:101:1-201203145710
Keywords: I0; H0; 330; international health; labor markets; Gesundheit; Sozialer Status; Alte Menschen; Vergleich; Welt